2009
DOI: 10.1159/000235241
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Studies: Prospective versus Retrospective

Abstract: Cohort studies form a suitable study design to assess associations between multiple exposures on the one hand and multiple outcomes on the other hand. They are especially appropriate to study rare exposures or exposures for which randomization is not possible for practical or ethical reasons. Prospective and retrospective cohort studies have higher accuracy and higher efficiency as their respective main advantages. In addition to possible confounding by indication, cohort studies may suffer from selection bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
212
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(217 citation statements)
references
References 75 publications
2
212
0
3
Order By: Relevance
“…Most research activities performed by responder trainees were retrospective clinical studies, which are a time-efficient and easy way of answering new questions with existing data but still have a higher tendency for non-publication. 32 However, we strongly feel that retrospective studies are important pillars for preparing trainees for understanding and asking questions regarding root-cause analyses of suspect events, developing skills to understand and derive actionable meanings from existing datasets, and creating a platform for subsequent studies of experimental designs in their future career. Also, consistent with previous experiences, 11,15,20 our study identified that laboratory-based research has a very high likelihood of publication.…”
Section: Discussionmentioning
confidence: 99%
“…Most research activities performed by responder trainees were retrospective clinical studies, which are a time-efficient and easy way of answering new questions with existing data but still have a higher tendency for non-publication. 32 However, we strongly feel that retrospective studies are important pillars for preparing trainees for understanding and asking questions regarding root-cause analyses of suspect events, developing skills to understand and derive actionable meanings from existing datasets, and creating a platform for subsequent studies of experimental designs in their future career. Also, consistent with previous experiences, 11,15,20 our study identified that laboratory-based research has a very high likelihood of publication.…”
Section: Discussionmentioning
confidence: 99%
“…Although this design suffers from a risk of losing some cases and necessary records, it is still worth undertaking in this setting as there are no previous publications on the studied subject [15]. …”
Section: Methodsmentioning
confidence: 99%
“…We restricted the review to include only prospective studies with consecutive or randomized sampling. Prospective studies are more easily controlled, and allow more rigorous methodologies including the use of blinding (Euser et al 2009). The exclusion of retrospective studies significantly reduced the number of studies included in this review, as retrospective studies are more widely reported (Mihai, Simon & Hellman 2009) and prospective studies are less frequently reported due to long data collection periods when this study design is used.…”
Section: Discussionmentioning
confidence: 99%